2023
DOI: 10.1186/s13045-023-01440-6
|View full text |Cite
|
Sign up to set email alerts
|

Elevated plasma levels of IL-6 and MCP-1 selectively identify CML patients who better sustain molecular remission after TKI withdrawal

Abstract: Treatment-free remission (TFR) in chronic myeloid leukemia (CML) is safe under adequate molecular monitoring, but questions remain regarding which factors may be considered predictive for TFR. Argentina Stop Trial (AST) is a multicenter TFR trial showing that 65% of patients sustain molecular remission, and the prior time in deep molecular response (DMR) was associated with successful TFR. Luminex technology was used to characterize cytokines in plasma samples. Using machine learning algorithms, MCP-1 and IL-6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
(10 reference statements)
2
2
0
Order By: Relevance
“…The severity of infection can be partially identified by the expression level of IL-6 according to earlier research [36]. However, while the results from the present study align with the majority of studies confirming the detrimental signaling promoted by elevated levels of IL-6, another study demonstrated that low levels of IL-6 are associated with an 8-fold higher risk of relapse in patients in treatment-free remission (TFR) of CML [37].…”
Section: Discussionsupporting
confidence: 82%
“…The severity of infection can be partially identified by the expression level of IL-6 according to earlier research [36]. However, while the results from the present study align with the majority of studies confirming the detrimental signaling promoted by elevated levels of IL-6, another study demonstrated that low levels of IL-6 are associated with an 8-fold higher risk of relapse in patients in treatment-free remission (TFR) of CML [37].…”
Section: Discussionsupporting
confidence: 82%
“…For these patients, baseline characteristics and treatment information are shown in Figure 1C . Regarding clinical variables, only prior time in deep molecular response (DMR) and treatment duration were significantly associated with the probability of successful TFR in our cohort, as we have recently published ( 12 ). Since NK cell receptors play a key role in target recognition and transmission of activating or inhibitory signals after binding to their ligands, we thus decided to examine the expression of a large panel of NK cell receptors, both at the time of discontinuation as well as at specific subsequent time points (3 and 12 months).…”
Section: Resultssupporting
confidence: 54%
“…The study was conducted as a sub-study of the Argentina Stop Trial (AST) registered in the National Registry of Health Research (RENIS: ISO02688) ( 12 ). For this prospective, single-arm, open-label, nonrandomized trial, we enrolled 46 patients with CP-CML at 7 Argentinean centers in Buenos Aires city and 3 more provinces (Buenos Aires province, Mendoza and Entre Rios).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation